Drying–rewetting cycles release phosphorus from forest soils1. Issue 5 (10th August 2016) - Dinh, Mai‐Van; Schramm, Thilo; Spohn, Marie; Matzner, Egbert
Abstract: Drying–rewetting cycles (D/W) occur frequently in topsoils and may mobilize phosphorus (P). We investigated the effect of repeated D/W on the release of dissolved inorganic (DIP) and organic P (DOP) from forest floors and A horizons. Samples were taken from 3 European beech sites and from 3 Norway spruce sites. Soils were desiccated up to pF 6 (–100 MPa) in three D/W cycles in the laboratory, while the controls were kept permanently at 50% water holding capacity. After each drying, P was extracted from the soils in water. D/W caused the release of DIP and DOP especially from O layers. There was no general difference in response to D/W between samples from beech and spruce. The net release of DIP after D/W was largest from the Oe horizons (average 50–60 mg P kg −1 ) for both beech and spruce forest soils. The net release of DIP from Oi layers was on average 7.8 mg P kg −1 and from spruce Oa layers 21.1 mg P kg −1 . In the A horizons, net DIP release was similar in beech and spruce soils with 0.4 mg P kg −1 . The release of DOP was less than the release of DIP except for the A horizons. Repeated cycles did not increase the release of DIP and DOP. The release of DIP and DOP was positively correlated with the microbial biomass in Oe and Oa layers but not in Oi layers. Our results suggest that D/W may significantly influence the short term availability of dissolved P in both beech and spruce forest soils.